CHANGE OF EPIDEMIOLOGICAL SITUATION OF COLORECTAL CANCER IN KAZAKHSTAN AFTER INTRODUCTION OF SCREENING - D.R. KAYDAROVA; A.ZH. ZHYLKAYDAROVA; A.A. AKHETOV; N.A. SHANAZAROV; K.U. BATYRBEKOV (Avicenna Tajik State Medical University, 2018)
Objective: To assess the change in the epidemiological situation of colorectal cancer (CRC) in Kazakhstan after the introduction of screening. Methods: Retrospectively, according to regional reports on endoscopic screening conducted an analysis general morbidity of CRC in the regions of the Republic of Kazakhstan. Results: The highest incidence of CRC in Kazakhstan was registered in Pavlodar (14.5%), North Kazakhstan (14.1%), Almaty (12.1%), Kostanay (11.5%), East Kazakhstan (11.0%), Karaganda (10.7%), Akmola (10.1%) regions and Astana City (8.8%). The average indicator for the Kazakhstan as a whole was 11.6%. Our data confirmed the fact that CRC is more often registered among males. In the analysis of the age-specific incidence of CRC, it is revealed the increase with age this peak morbidity falls on the age category over 70 years. Unit weight indicators of I-II, III and IV stages of newly identified cases of CRC for 2004-2014 clearly shows an increase in the specific weight of the I-II stage by almost 2 times (from 35% to 67.4%) by reducing for the specified period of specific weight of IV stages from 19.3% to 13.1% and stage III more than 2 times (from 45.7% to 19.5%). Conclusion: The analysis of the prevalence of CRC, both in the regions and in the Republic of Kazakhstan as a whole, has shown an increase of morbidity rates of given pathology. The stage-by-stage prevalence of morbidity shows its increase due to the I and II stages from 2011 when the population screening of CRC was introduced. This allows to speak about the positive economic effect of screening since the treatment of I and II stages of CRC requires significantly less funds.